Comic Video Learning Media in Science Content: Nature of Objects and Their Changes - Manik, Yunda; I Wayan Widiana (Mimbar Ilmu, 2023)
The absence of innovative learning media has resulted in students' science learning outcomes not being achieved optimally. This research aims to produce a design and test the validity, practicality, and effectiveness of comic video learning media. This research uses the ADDIE development model. The subjects of this research were 2 experts, 1 practitioner, and 1 group of fifth-grade elementary school students. In contrast, the research object was comic video learning media on science content, material about the properties of things and their changes. The data collection methods used are questionnaires to measure the validity and practicality of the media developed and multiple choice questions to measure students' science learning outcomes. The data analysis techniques used are qualitative analysis and quantitative analysis. The results of this research show that producing a product in the form of comic video learning media on science content material about the nature of objects and their changes, the amusing video learning media obtained very good validity with an achievement level of 90% by material experts and 93.33% from media experts, achieving a level of practicality. Amounted to 96.67% by practitioner responses, 97.5% by students in individual tests, and 98.75% by small group tests. It was concluded that comic video learning media effectively improved students' science learning outcomes. This research has implications for students' interest in learning and increasing the quality of lessons.